Knowledge, attitudes and practices of cervical cancer prevention among Zambian women and men - Anayawa Nyambe; Jarl K. Kampen; Stridutt K. Baboo; Guido Van Hal (BMC, 2019)
Abstract Background In Zambia, cervical cancer screening was started in 2006 and the human papillomavirus vaccine was piloted in 2013. Nevertheless, cervical cancer remains the leading cancer. It is assumed that knowledge, social interaction, health behaviors and religion are factors that can influence screening and vaccination practices. This study addresses the question, what is the relationship between knowledge about cervical cancer, attitudes, self-reported behavior, and immediate support system, towards screening and vaccination of cervical cancer of Zambian women and men. The results of this study serve as a basis for future research, an input for improvement and adjustment of the existing prevention program and build on documented health behavior frameworks. Methods A cross-sectional mixed methods study was conducted from February to May 2016. Two separate questionnaires were used to collect data from women (N = 300) and men (N = 300) residing in Chilenje and Kanyama (two townships in the capital city Lusaka). Respondent's knowledge of cervical cancer was operationalized by grading their ability to correctly identify causes and protective factors if they were aware of cervical cancer. Besides providing descriptive statistics of all study variables, we tested four research hypotheses concerning the link between knowledge, attitudes and practices suggested by the literature, by applying appropriate statistical tests (chi square test, analysis of variance, logistic regression). Results Less than half of the respondents (36.8%) had heard of cervical cancer, 20.7% of women had attended screening and 6.7% of the total sample had vaccinated their daughter. Knowledge of causes and prevention was very low. There was a strong association between having awareness of cervical cancer and practicing screening (odds ratio = 20.5, 95% confidence interval = [9.214, 45.516]) and vaccination (odds ratio = 5.1, 95% confidence interval = [2.473, 10.423]). Social interactions were also found to greatly influence screening and vaccination behaviors. Conclusions The low level of knowledge of causes and prevention of cervical cancer suggests a need to increase knowledge and awareness among both women and men. Interpersonal interactions have great impact on practicing prevention behaviors, for instance, vaccination of daughters.